Best Practices in Pharmacotherapy for Acute Coronary Syndromes - Robert Barcelona (US Cardiology Review)
Numerous advances have been made in the therapy of acute coronary syndromes. Despite these advances, acute coronary syndromes still cause significant morbidity and mortality. Decisions as to the best therapy vary depending on other patient factors, such as age, need for chronic anticoagulation, tolerability of medications, and the degree of myocardial damage. Recent evidence suggests that a shorter duration of therapy may be beneficial in decreasing bleeding events without compromising benefits of preventing ischemic complications. For those who have an indication for chronic anticoagulation, less intensive therapy may also be beneficial, again without increasing ischemic complications. Data regarding agents that inhibit the renin–angiotensin–aldosterone system are available and these data are reviewed. Knowledge of the pharmacology, potency, and pharmacokinetics of drugs, as well as adverse drug events, may direct clinicians in choosing the optimal pharmacotherapy strategy for their patients.